2012
DOI: 10.1002/dneu.20977
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel rat neural progenitor clone that expresses dlx family transcription factors and gives rise to functional gabaergic neurons in culture

Abstract: GABAergic interneurons are lost in conditions including epilepsy and CNS injury, but there are few culture models available to study their function. Towards the goal of obtaining renewable sources of GABAergic neurons, we used the molecular profile of a functionally-incomplete GABAergic precursor clone to screen 17 new clones isolated from GFP+ rat E14.5 cortex and ganglionic eminence (GE) that were generated by viral introduction of v-myc. The clones grow as neurospheres in medium with FGF2, and after withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…We cultured the three cell types, attempting to keep them as homogenous as culturing methods would permit. The CTX8 radial glial cell line, which possesses the capability to differentiate into either glia or neurons, can be kept in an “undifferentiated” radial glial fate (Li et al, 2012). Cultures of E18 cortical neurons treated with AraC represented pure neurons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We cultured the three cell types, attempting to keep them as homogenous as culturing methods would permit. The CTX8 radial glial cell line, which possesses the capability to differentiate into either glia or neurons, can be kept in an “undifferentiated” radial glial fate (Li et al, 2012). Cultures of E18 cortical neurons treated with AraC represented pure neurons.…”
Section: Resultsmentioning
confidence: 99%
“…These GFP-positive cells were isolated from E14.5 cortices of rats expressing GFP under control of the β-actin promoter and were selected for their radial glial characteristics, which can be maintained in medium containing basic fibroblast growth factor (Li et al, 2012). CTX8 cells can also differentiate into both neurons and astroglia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous report has demonstrated that GE6 cells proliferate rapidly in culture in the presence of FGF2 and differentiate into primarily neurons with little astroglia upon FGF2 withdrawal 30 . In the current study, we aim to determine if this distinct neurogenic potential of GE6 still holds after transplantation into the postnatal brain.…”
mentioning
confidence: 99%